2021
DOI: 10.3389/fphar.2021.700366
|View full text |Cite
|
Sign up to set email alerts
|

SGLT1 Knockdown Attenuates Cardiac Fibroblast Activation in Diabetic Cardiac Fibrosis

Abstract: Background: Cardiac fibroblast (CF) activation is a hallmark feature of cardiac fibrosis in diabetic cardiomyopathy (DCM). Inhibition of the sodium-dependent glucose transporter 1 (SGLT1) attenuates cardiomyocyte apoptosis and delays the development of DCM. However, the role of SGLT1 in CF activation remains unclear.Methods: A rat model of DCM was established and treated with si‐SGLT1 to examine cardiac fibrosis. In addition, in vitro experiments were conducted to verify the regulatory role of SGLT1 in prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…This is in line with the study of Kashiwagi et al [ 67 ] showing a diffuse positive staining of SGLT1 in tissues obtained from all four chambers of human autopsied hearts. A similar pattern confined to cardiomyocytes was reported in healthy and diabetic rat hearts [ 64 ]. On the single cell level, studies confirmed that cardiomyocytes isolated from normal and diabetic hearts [ 54 ], and from HL-1 cardiac cell line (murine atrial cardiomyocytes) [ 55 ] express high levels of SGLT1 in the membrane.…”
Section: Localization Of Myocardial Sglt1supporting
confidence: 84%
See 1 more Smart Citation
“…This is in line with the study of Kashiwagi et al [ 67 ] showing a diffuse positive staining of SGLT1 in tissues obtained from all four chambers of human autopsied hearts. A similar pattern confined to cardiomyocytes was reported in healthy and diabetic rat hearts [ 64 ]. On the single cell level, studies confirmed that cardiomyocytes isolated from normal and diabetic hearts [ 54 ], and from HL-1 cardiac cell line (murine atrial cardiomyocytes) [ 55 ] express high levels of SGLT1 in the membrane.…”
Section: Localization Of Myocardial Sglt1supporting
confidence: 84%
“…In line with data on human hearts, myocardial SGLT1 mRNA or protein expression was found to be upregulated in non-diabetic small animal models of acute myocardial ischemia–reperfusion injury [ 55 ] or ischemic preconditioning [ 56 ], permanent LAD ligation (model of ICM) [ 51 , 57 , 58 ], and hemodynamic-overload induced HF [ 59 , 60 ], as well as in models of metabolic syndrome and T2DM [ 51 , 54 , 61 , 62 , 63 , 64 ]. Interestingly, SGLT1 was downregulated in mice with streptozotocin-induced type 1 diabetes mellitus (T1DM) [ 51 ].…”
Section: Changes In Expression Of Sglt1 In Various Myocardial Disease Statesmentioning
confidence: 99%
“…In these patients, LV SGLT1 expression was independently associated with the extent of LV dilation and systolic dysfunction [2], highlighting the clinical relevance of upregulation of LV SGLT1 in HF. Similarly, previous studies noted that SGLT1 expression was upregulated in non-diabetic small animal models of acute myocardial ischemia-reperfusion injury [7], and permanent left anterior descending coronary artery ligation (model of ischemic heart disease) [1,31], as well as in models of metabolic syndrome/T2DM [1,4,5,30]. Matsushita et al [3] reported that in nondiabetic mice with pressure overload (TAC) for 6 weeks, LV mRNA expression of SGLT1 was significantly upregulated, together with those of the pathological markers CTGF and Col1a1.…”
Section: Discussionmentioning
confidence: 54%
“…In this study, we report for the first time that this increased expression of Nox4 in pressure and volume overload-induced HF is strongly correlated with the increase in expression of SGLT1, in line with substantially higher levels of nitro-oxidative stress and upregulation of TGF-β. Importantly, recent studies found that upregulation of SGLT1 is profibrotic [4,43], its knockdown in rats with T2DM reduces myocardial collagen expression and fibrotic accumulation [4]. Therefore, a functional link might exist between upregulation of myocardial SGLT1 in HF, increased nitro-oxidative stress, and the development of cardiac fibrosis, which needs to be further elucidated.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation